Contributions of Christianity to Humanity’s Civilization: Review on Alvin J. Schmidt’s Under the Influence: How Christianity Transformed Civilization - ZHANG, Jian (Journal of Research for Christianity in China (JRCC), 2025)
The Christianity, since it formed, always opposed against the various barbarous, backward and ignorant habits and traditions, such as infanticide by drawing and abandoning infants, gladiatorial shows, suicide, promiscuous heterosexual sex, homosexuality, pederasty, child marriage, polygamy, widows buried alive, foot binding of women, slavery, etc.. The Christianity too advocated universal love, compassion, charity and praised highly arts. The Christianity made positive contributions to Humanity’s Civilization and social progress and made itself developing gradually to a most civilized religion which has the biggest power and influence in the world. Alvin J. Schmidt’s Under the influence: how Christianity transformed civilization expounds these completely, systematically, deeply and concentratedly, and becomes a synthesized work.
Keywords: The Christianity, Various corrupt customs, Humanity’s Civilization; Under the influence